Inventarisasi Tumbuhan Obat di Jalur Pendakian Gunung Ungaran - Muhamad Khoirurrais; Ismail Ismail; Baiq Farhatul Wahidah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Mount Ungaran has a high varied vegetation which includes medicinal plants. The purpose of this study is to know the types of medicinal plants found in the hiking trails of Mount Ungaran. The method used in this research is the cruising method. The object of research was spermatophyta medicinal plants. Data collection techniques used in this study are observation, characterization and document review. The results of the study obtained 43 types of medicinal plants belonging to 30 families with the most families were Asteraceae family with the number of 5 species. But unfortunately these plants have not been maximally utilized by the surrounding community due to lack of community knowledge about the potential of these plants and their use especially as a medicinal plants.